EFFECTIVENESS OF THE STROKE-EASE PROGRAM USING ABDOMINAL STIMULATION AND EXERCISE TO MANAGE CONSTIPATION IN POST-THROMBOLYSIS STROKE PATIENTS - Asrianti, Ade; Natashia, Dhea; Nursanti, Irna; Azzam, Rohman (Universitas Kadiri, 2026)
Constipation is a frequent complication among post stroke patients and is often worsened by immobility, medication effects, dietary limitations, and neurological impairments. Effective bowel management is essential to improve comfort, prevent additional complications, and support recovery. Aims to evaluate the effectiveness of the STROKE EASE intervention in reducing constipation severity among post stroke patients who received thrombolysis. A quasi experimental pretest posttest study was conducted involving thirty post stroke patients in a private hospital in East Jakarta. Demographic and clinical data were collected, including age, sex, functional independence, diet type, comorbidities, muscle strength, and National Institutes of Health Stroke Scale score. Constipation severity was measured using the Constipation Assessment Scale before and after the intervention. Changes in scores were analyzed using paired samples t tests. The mean age of participants was 64.03 years with almost equal distribution between men and women. Most patients required partial assistance with daily activities and consumed a soft diet. Nearly all had comorbid hypertension or diabetes. The mean National Institutes of Health Stroke Scale score was 6.50. Constipation Assessment Scale scores decreased significantly from 11.00 before the intervention to 2.53 after the intervention with p less than 0.001. STROKE EASE intervention significantly reduced constipation severity in post thrombolysis stroke patients. This evidence based nursing approach offers a practical method to improve bowel function and patient comfort. Further studies with larger samples are recommended.